Sex-Specific Involvement of Estrogen Receptors in Behavioral Responses to Stress and Psychomotor Activation - Georgiou, Polymnia; Zanos, Panos; Jenne, Carleigh E.; Gould, Todd D. (Frontiers in Psychiatry, 2019)
Fluctuating hormone levels, such as estradiol might underlie the difference in the prevalence of psychiatric disorders observed in women vs men. Estradiol exert its effects primarily through binding on the two classical estrogen receptor subtypes, alpha (ERα) and beta (ERβ). Both receptors have been suggested to a have role in the development of psychiatric disorders, however, most of the current literature is limited to their role on females. We investigated the role of estrogen receptors on cognition (novel-object recognition), anxiety (open-field test, elevated-plus maze and light/dark box), stress-responsive behaviors (forced-swim test, learned helplessness and sucrose preference), pre-pulse inhibition (PPI) and amphetamine-induced hyperlocomotion in both male and female mice either lacking the ERα or ERβ receptor. We found that female Esr1-/- mice have attenuated pre-pulse inhibition, whereas female Esr2-/- mice manifested enhanced pre-pulse inhibition. No pre-pulse inhibition difference was observed in male Esr1-/- and Esr2-/- mice. Moreover, amphetamine-induced hyperlocomotion was decreased in male Esr1-/-, but not Esr2-/- mice, while female Esr1-/- and Esr2-/- mice showed enhanced response. Genetic absence of ERα did not alter the escape capability or sucrose preference following inescapable shock in both male and female mice. In contrast, female, but not male Esr2-/- mice, manifested decreased escape failures compared with controls. Lack of Esr2 gene in male mice was associated with decreased sucrose preference following inescapable shock, suggesting susceptibility for development of anhedonia following stress. No sucrose preference differences were found in female Esr2-/- mice following inescapable shock stress. Lastly, we demonstrated that lack of Esr1 or Esr2 genes had no effect on memory and anxiety-like behaviors in both male and female mice. Our findings indicate a differential sex-specific involvement of estrogen receptors in the development of stress-mediated maladaptive behaviors as well as psychomotor activation responses suggesting that these receptors might act as potential treatment targets in a sex-specific manner.